Cytokine Release Syndrome: Current Perspectives - Murthy H (ImmunoTargets and Therapy, 2019)
Hemant Murthy,1 Madiha Iqbal,1 Julio C Chavez,2 Mohamed A Kharfan-Dabaja1 1Division of Hematology-Oncology and Blood and Marrow Transplantation Program, Mayo Clinic, Jacksonville, FL, USA; 2Department of Malignant Hematology, Moffitt Cancer Center, Tampa, FL, USACorrespondence: Mohamed A Kharfan-DabajaDivision of Hematology-Oncology and Blood and Marrow Transplantation Program, Mayo Clinic, 4500 San Pablo Road, Mangurian Bdg 3rd Floor, Jacksonville, FL 32224, USATel +1 904 953-2000Email KharfanDabaja.Mohamed@Mayo.EduAbstract: Chimeric antigen receptor T cell (CART) therapy represents a novel and a paradigm-shifting approach to treating cancer. Recent clinical successes have widened the applicability of CD19 CART cells for the treatment of relapsed/refractory B-cell NHL, namely tisagenleclucel and axicabtagene ciloleucel. Tisagenleclucel is also approved for relapsed and/or refractory B-ALL up to age 25. CART therapy is associated with unique and potentially life-threatening toxicities, notably cytokine release syndrome (CRS). A better understanding of the pathogenesis of CRS is crucial to ensure proper management. In this review, CRS definitions, profiles, risk factors and grading systems are discussed. Finally, current and novel investigational approaches and therapies for CRS are summarized.Keywords: cytokine release syndrome, chimeric antigen receptor T-cell therapy